An Empirical Approach Leveraging Tumorgrafts to Dissect the Tumor Microenvironment in Renal Cell Carcinoma Identifies Missing Link to Prognostic Inflammatory Factors - Tao Wang; Rong Lü; Payal Kapur; Bijay S. Jaiswal; Raquibul Hannan; Ze Zhang; Iván Pedrosa; Jason J. Luke; He Zhang; Leonard D. Goldstein; Qurratulain Yousuf; Yi-Feng Gu; et al. (2018)
By leveraging tumorgraft (patient-derived xenograft) RNA-sequencing data, we developed an empirical approach, DisHet, to dissect the tumor microenvironment (eTME). We found that 65% of previously defined immune signature genes are not abundantly expressed in renal cell carcinoma (RCC) and identified 610 novel immune/stromal transcripts. Using eTME, genomics, pathology, and medical record data involving >1,000 patients, we established an inflamed pan-RCC subtype (IS) enriched for regulatory T cells, natural killer cells, T